Criminal Aspects in Regulating Street Vendors (PKL) In Kendari City - Muharam, Rully (International Journal of Management and Education in Human Development, 2025)
a research method is used, namely normative legal research (Normative Juridical) which is conducted by examining library materials or primary data, secondary data, and tertiary data. This research was conducted to identify the concepts and principles as well as legal principles used to regulate. The thinking method used is the deductive method, namely a way of thinking in drawing conclusions drawn from something general that has been proven to be true and the conclusion is aimed at something specific. The criminal aspects of street vendor enforcement are complex and require in-depth study. Street vendor enforcement must prioritize a persuasive and educational approach, while considering the street vendors' rights to work and engage in business, and the local government's obligation to provide alternative solutions. By understanding the complexities of the criminal aspects of street vendor enforcement in Kendari City, we hope to be motivated to seek just and sustainable solutions. Solutions that prioritize not only enforcement of regulations but also consider the rights and needs of street vendors to live and work decently. So far, criminal handling of street vendor control has not been in accordance with existing regulations and provisions, as stated in Article 351 paragraph 3 (Criminal Code), which states that those who violate this Article will be subject to a maximum imprisonment of seven years. Currently, the only sanction given is a warning. Due to the ineffectiveness of these sanctions, violent crimes committed by civil service police are still common and frequently encountered in Kendari City